有了
第一题是:a)用数学归纳法证明:1*3+3*5+5*7+……+(2n-1)(2n+1)=[(2n-1)(2n+1)(2n
3个回答
相关问题
-
用数学归纳法证明:1-3+5-7+...+(-1)^N-1(2N-1)=(-1)^N-1*N
-
用数学归纳法证明1+3+5+……+(2n-1)=n^2
-
用数学归纳法证明:1+3+5+…+(2n-1)=n2.
-
用数学归纳法证明1+3+5+.+(2n-1)=n^2
-
用数学归纳法证明:1*3*5*……*(2n-1)*2^n=(n+1)(n+2)……(2n)(n属于自然数)
-
用数学归纳法证明:1*3*5*……*(2n-1)*2^n=(n+1)(n+2)……(2n)(n属于自然数)
-
用数学归纳法证明:1平方/(1*3)+2平方/(3*5)+…n平方/[(2n-1)(2n+1)]=n(n+1)/2(2n
-
用数学归纳法证明1 1+2+3+.+n=1/2*n*(n-1) 2 n为正整数1+3+5+……+(2n-1)=n^2
-
用数学归纳法证明1+4+7+...+(3n-2)=[n(3n-1)]/2
-
数学归纳法题证明:1+1/2+1/3+……+1/(2^n-1)>n/2 用数学归纳法.